Struktur Dan Pengaruh Teks Akademik Dan Non-Akademik Dalam Meningkatkan Pemahaman Mahasiswa Pada Proses Pembelajaran - Ferozi Ramdana Irsyad; Noubel Putra Nainggolan; Rona Hinirim Gultom; Arsiska Sari; Fitriani Lubis (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This research aims to explore the influence of two types of text, namely academic and non-academic, on student understanding in the learning context. Involving Medan State University (UNIMED) students, this research used a Google Form questionnaire as a data collection tool. The research results show that the use of non-academic texts can increase student interest and involvement, while the combination of academic and non-academic texts is considered effective for broadening insight and understanding of learning material. The conclusions of this study highlight the importance of flexibility in learning approaches, emphasizing that a diversity of text types is key to achieving effective education.